Pengaruh Model Pembelajaran Science Environment Technology and Society (SETS) Terhadap Sikap Peduli Lingkungan Siswa pada Pembelajaran IPAS Sekolah Dasar - Putri, Tia Egi Giana; Erlisnawati, Erlisnawati; Marhadi, Hendr (Journal of Education Technology Information Social Sciences and Health, 2025)
This study aims to determine the influence of the Scince Environment Technology and Society (SETS) learning model on the attitude of environmental care of students IV of SD 017 Jaya Kopah. This study is an experimental type of quantitative research with the Design One Group Pretest-Posttest method. The variables of this study consist of an independent variable, namely Scince Environment Technology and Society (SETS) and the bound variable is environmental care attitude. The sample of this study is grade IV students of SD Negeri 017 Jaya Kopah. The data collection technique is by questionnaire of environmental care attitudes and documentation. The data analysis techniques used consisted of normality tests, homogeneity tests, and hypothesis tests with the help of IBM SPSS Statistic 22. The results of this study show that there is a significant influence of the application of the Scince Environment Technology and Society (SETS) learning model on the attitude of caring for the environment of grade IV students of SD Negeri 017 Jaya Kopah. This is shown by the results of data analysis using the SPSS program, it is known that the significance of the paired t-test is 0.001 so that it is said that Ho is rejected and Ha is accepted. Therefore, it was concluded that there was a difference in students' attitudes of caring for the environment before and after learning. This is also supported by the results of the percent correlation test from the pretest and posttest results where a score of 78.0% was obtained, which means that this learning model is effective in improving students' attitudes towards caring for the environment.